The Analysis of Food Consumption Pattern in Low-Income Households in Korumba Village Mandonga District Kendari City - Rahmad Rahmad; Sitti Aida Adha Taridala; Weka Gusmiarty Abdullah (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2022)
This study aims to determine the food consumption patterns of low-income households in Korumba Village, Mandonga District, Kendari City. The research took place from June 2021 to May 2022, with a total of 74 respondents who were determined by purposive sampling technique. The data used in this study are primary data and secondary data. Variables in this study include age, education level, number of family members, occupation, type, and amount of food consumed (food sources of carbohydrates, side dishes, vegetables, and fruits). The data analysis used is descriptive qualitative. The results showed that the food consumption patterns of respondents in the Korumba Village varied both in the amount and type of food they consumed, and all respondents in the Korumba Village consumed food according to their household needs, such as food sources of carbohydrates, side dishes, vegetables, fruits, and other sources of drinking water. However, the amount of food consumed by low-income households in Korumba Village has not met the needs of their families.